The Influences of Normal Load Variation in Direct Shear Strength Test Parameters Tuff from Candi Ijo Yogyakarta - Saptono, Singgih; Gilang Trilaksono, Rahmatyo; Adi Siswanto, Waluyo (International Journal of Engineering and Technology, 2019)
This paper presents direct shear strength test results of tuff taken from Candi Ijo of Jogjakarta, Indonesia where the slopes are considered in critical condition and need attention. Serial shear tests were conducted to find the normal loads appropriate for direct shear strength test. The optimum set of normal loads on direct shear strength test for tuff from Candi Ijo were tried by analyzing Mohr & Coulomb criterion against Hoek-Brown criterion. The study shows that excessive normal load may initiate crack caused by a failure on direct shear strength test due to the generated shear stress as well as the normal stress. This can be indicated by the unacceptable high value of cohesion (c) and the low internal friction angle (ϕ). The maximum limit of normal stress (σn) on direct shear strength test 12.5% σc for Indonesia general area is still applicable for the case of Candi Ijo. This research work recommends applying normal loads for direct shear strength test of tuff are 0.4 kN, 0.6 kN and 0.8 kN. This recommendation was also supported by the analysis using graph suitability of Mohr & Coulomb criterion and Hoek-Brown criterion.